ESTIMATION OF SOYBEAN SEED (Glycine max L. Merr) DETERIORATION DURING STORAGE - Irma Noviana; IGP Alit Diratmaja; Abdul Qadir; Faiza C Suwarno (Fakultas Pertanian, Universitas Janabadra, 2017)
Soybean seeds able to degradation during storage. The aims of study were to studying the behavior and deterioration of soybean seed and to predict seed viability during storage in controlled conditions. The experiment used completely randomized design with two levels of variety which nested in storage period with four replications. Two varieties were Dering-1 and Detam 2 that storage in controlled condition at temperature of 19 up to 22 °C and 64 up to 67 percent of relative humidity for six months. The seeds were evaluated for moisture content, protein, peroxide value, electrical conductivity and seed viability. During the deterioration the moisture content, peroxide, electrical conductivity increased while protein content and germination declined. Deterioration model of soybeans can be used to predict the decline of soybean seeds during the controlled storage